Internationalisation ou nationalisation ? - Valentin Behr (Revue d’Histoire des Sciences Humaines)
The neo-liberal higher education and research reforms undertaken in the 1990s by the first Polish governments of the post-Communist era led to a process of relative privatisation of higher education. In the framework of Poland's inclusion in the European Higher Education Area, a new wave of reforms encouraged competition between universities. In 2010-2011, bibliometric critera for evaluating the academic performance of researchers and institutions was formally adopted. When the Law and Justice party (PiS) came to power in 2015, competitiveness and efficiency were emphasised further, with an added ideological dimension which was explicitly national-conservative. This article presents the main developments in Polish higher education and research since 1989, and discusses in greater depth the PiS’s policies.